Initial reef building in the oceanic barrier reef of Elbingerode, Mid-Devonian, Harz Mts., Germany - Eberhard Gischler; Arnold Fuchs (Palaeobiodiversity and Palaeoenvironments, 2026)
The Elbingerode reef complex is a Devonian reef system in the Harz Mountains and well known for its thick and fossil-rich limestones that formed an oceanic barrier reef system in the Rhenohercynian Basin. The initial reef building of this barrier reef system, exposed in the form of small outcrops at the tops of underlying marginal and central volcanic highs is less well known and reflected in the occurrence of biogenic packstones, grainstones, and wackestones deposited in close relationship to volcanic activity. The limestones from marginal volcanic highs are rich in crinoidal debris (as the main constituent particle), and contain remains of brachiopods, rugose and tabulate corals, bryozoa, trilobites, tentaculites, ostracods, conodonts, goniatites, and holothurians. Intraclasts and clasts of volcanic rocks are common. The fine-grained matrix contains 60-80% carbonate and considerable amounts of non-carbonate fines. The common occurrence of a highly diverse fauna is evidence of a thriving level-bottom community in a stressed environment including volcanic activity and possibly reduced water transparency and pH. The textures and fabrics encountered suggest deposition below the fair-weather wave base, i.e. in water depths of a few tens of meters. In contrast, the slightly younger initial limestones of central volcanic highs are in places dominated by stromatoporoids and tabulate corals in grain-supported textures, suggesting deposition in shallower water as compared to the marginal volcanic highs. The phase of initial reef accretion ranged from the higher hemiansatus -Zone to the lower varcus- Zone of the conodont zonation, predating barrier-reef development, which started during the middle varcus -Zone (Givetian).